Prevalence of idiopathic normal pressure hydrocephalus in older adult population in Shanghai, China: A population‐based observational study - Fang, Xuhao; Xu, Xinxin; Liu, Chunyan; Li, Shihong; Deng, Yao; Tang, Feng; Zhang, Li; Xing, Yan; Mao, Renling; Hu, Jin (Alzheimer's & dementia, 2025)
INTRODUCTION Idiopathic normal pressure hydrocephalus (iNPH), a condition that primarily affects the elderly, has an unclear prevalence rate in China. METHODS A cross‐sectional survey involving 1491 seniors aged 60 and above in Shanghai was conducted. Clinical symptoms and brain imaging data were collected for the diagnosis of suboptimal probable iNPH (s‐probable iNPH). The crude prevalence was calculated and the estimated prevalence was inferred. RESULTS The crude prevalence of s‐probable iNPH was 3.09% and 2.62% respectively, using DESH score ≥6 and Radscale score ≥7 as the primary imaging diagnostic criteria. The estimated prevalence of Shanghai was 2.59% among people over 60 years old and it rose to 7.99% among people aged over 90, and it was estimated that 134,152 and 11,708, respectively, had s‐probable iNPH among the corresponding age group. DISCUSSION The prevalence of s‐probable iNPH fluctuates based on the radiological scoring systems and the defined thresholds employed, and it tends to rise with advancing age. Highlights **Significant Prevalence**: The study identified a substantial prevalence of iNPH in older adults, with rates increasing significantly with age, particularly among those aged 90–99 years and centenarians. **Diagnostic Approach**: The research utilized novel diagnostic methodologies by integrating the DESH score or Radscale score with stringent clinical symptoms, providing a closer approximation to the true prevalence of iNPH. **Gender Disparity**: A marked gender difference was observed, with the prevalence of iNPH being significantly higher in males compared to females across all age groups. **Clinical Implications**: The findings underscore the importance of considering iNPH in the differential diagnosis of dementia, particularly among older male patients presenting with cognitive impairment and gait disturbances. **Public Health Impact**: The estimated number of s‐probable iNPH patients in Shanghai highlights the need for increased awareness and better management strategies for this underdiagnosed condition in the aging population.